Factors that influence on the confrontation the spinal cord injury - Montserrat Melchor Arteaga; Lorena Fernández Sánchez; María Parro Jiménez; Ana María Sánchez Donaire (Fundación para el Desarrollo de la Enfermería, 2011)
Definitions of spinal cord injury agree in the consequences of that injury is the loss in varying degrees of autonomic function; this will cause a change in the lifestyle of patients and their families.In the spinal injury, the priority is the recovery or maintenance of vital organ functions, the physical stabilization for people. Later, the priority here is the rehabilitation and adaptation. This should be integrated at all levels, physical, psychological and social. Confrontation is, by Callista Roy, a important variable for understanding the effect of stress on health and disease, health maintenance or recovery. The way, that the patients have to confront the disease, are the confrontation strategies. They are defined as thoughts and actions that persons put in place to deal with adverse changes. They are grouped into 3 categories: problems, emotions and avoidance.There are others factors that influence in the use of strategies, between them the personality. According to Eysenck this is determined by the functional interaction of four factors: cognitive (intelligence), conative (character), affective (temperament) and somatic (construction). With this study we want to know the factors that influence in the confrontation of the spinal cord injury and to analyze the possible relation between them, and to be able to elaborate particular tools, on the most determinant factors, to obtain an effective confrontation about this type of disease.